Pain Management Providers in the Era of COVID-19: Who is Taking Care of Those Who Provide Care? - Toutin Dias G; Schatman ME (Journal of Pain Research, 2022)
Gabriela Toutin Dias,1 Michael E Schatman2– 4 1Psychology Assessment Center, Massachusetts General Hospital, Boston, MA, USA; 2Department of Anesthesiology, Perioperative Care and Pain Medicine, NYU School of Medicine, New York, NY, USA; 3Division of Medical Ethics, NYU School of Medicine, New York, NY, USA; 4School of Social Work, North Carolina State University, Raleigh, NC, USACorrespondence: Michael E SchatmanDepartment of Anesthesiology, Perioperative Care and Pain Medicine, NYU School of Medicine, 550 First Avenue, New York, NY, 10016, USATel +1 425-647-4880Email Michael.Schatman@NYULangone.org